2021
DOI: 10.17818/emip/2021/2.10
|View full text |Cite
|
Sign up to set email alerts
|

Examining Entrepreneurial Orientation – Performance Relationship Among Croatian Service Smes

Abstract: The relationship between entrepreneurial orientation and business performance has been widely researched. However, in scientific literature there is still a need for further clarification when observing the before mentioned concepts, especially within the service SME context. Likewise, when observing this relationship it is necessary to look into the impact of entrepreneurial orientation on individual segments of business performance, i.e. on financial and non-financial constructs. Therefore, the aim of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Empirical research confirms the above and suggests that EO's impact on business performance is stronger in a highly dynamic, uncertain, and hostile environment (Morić Milovanović et al 2021a;Bauweraerts 2018;Chirico and Bau' 2014;Wiklund and Shepherd 2005). Furthermore, Zahra (1993) found a negative relationship linking entrepreneurship and performance in the context of firms operating in solid and more predictable environments.…”
Section: The Interaction Of Entrepreneurial Orientation and Environme...supporting
confidence: 59%
“…Empirical research confirms the above and suggests that EO's impact on business performance is stronger in a highly dynamic, uncertain, and hostile environment (Morić Milovanović et al 2021a;Bauweraerts 2018;Chirico and Bau' 2014;Wiklund and Shepherd 2005). Furthermore, Zahra (1993) found a negative relationship linking entrepreneurship and performance in the context of firms operating in solid and more predictable environments.…”
Section: The Interaction Of Entrepreneurial Orientation and Environme...supporting
confidence: 59%
“…Endogenous integration theory can be seen as a sub-theory of neoclassical growth theory, which claims that the source of technological progress is the expansion of the market due to the scale effect. By expanding the market, investments in research and development are encouraged, the market becomes more competitive and efficient through better mobility of production factors (Morić Milovanović et al, 2021). The effect of growth based only on integration is the subject of numerous studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Veselinović et al (2021) also found that the EO-performance relationship is partially mediated by total quality management. Morić-Milovanović et al (2021), on a sample of 136 Croatian SMEs, using multiple linear regression analysis, showed the positive impact of EO on performance of service SMEs, expressed both as financial and nonfinancial performance indicators. Findings also imply environmental factors have no moderation effect on the EO-performance relationship (Morić-Milovanović et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2023, 13, 26 2 of 16 (Luu and Ngo 2019;Su et al 2011) and under the influence of various external factors such as environmental hostility (Morić-Milovanović et al 2021;Zahra and Garvis 2000), industry dynamism (Morić-Milovanović et al 2021;Rauch et al 2009) and investment intensity (Kohtamäki et al 2019). Tang et al's (2008) findings indicate that the EO-performance relationship might be moderated by institutional framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation